(untitled) (Journal of NELTA, 2022)
As English continues to spread as an international lingua franca, there is a growing diversity in its use around the world. As a result, there are calls for embracing the diversity in the teaching, learning and assessment of the language. At the same time, there is a growing criticism against the widely taken language tests such as the Test of English as a Foreign Language (TOEFL) and The International English Language Testing System (IELTS) for being guided by the pervasive ideology of monolingual native speakerism and devaluing the multilingual speakers and the multiple varieties of Englishers. Against this backdrop, this conceptual paper focuses on the inﬂuence of the World Englishes movement on these so-called standardized tests and critically examines how the existing assessment practices fail to represent the multilingual repertoires and actual language practices of the diverse range of test-takers around the world. Based on the critical analysis of relevant literature on World Englishes, the paper highlights the progress, challenges and possibilities for incorporation of more diverse models of language tests in a translingual world that we live in today.